2004
DOI: 10.1063/1.1639135
|View full text |Cite
|
Sign up to set email alerts
|

A uniform glow discharge plasma source at atmospheric pressure

Abstract: An atmospheric-pressure, uniform, continuous, glow plasma was produced in ambient air assisted by argon feeding gas, using a 13.56 MHz rf source. Based on the measured current–voltage curve and optical emission spectrum intensity, the plasma showed typical glow discharge characteristics, free from streamers and arc. The measured rotational and vibrational temperatures were in the range of 490 to 630 K and 2000 to 3300 K, respectively, within the operation range of argon flow rate and rf power. From the spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 10 publications
10
87
0
2
Order By: Relevance
“…At lowcurrent densities, the discharge current increases in proportion to the RF voltage across the electrode gap and the differential conductivity of the plasma is positive. This is similar to the mode in low-pressure glow discharges, and corresponds to the operation regime of most reported RF APGD experiments [1]- [7], [9], [16]. When the current density increases to a critical threshold, the discharge plasma evolves into a different operation regime in which the discharge current increases with decreasing gap voltage and the differential conductivity becomes negative [8].…”
Section: Current-voltage Characteristicsmentioning
confidence: 83%
See 2 more Smart Citations
“…At lowcurrent densities, the discharge current increases in proportion to the RF voltage across the electrode gap and the differential conductivity of the plasma is positive. This is similar to the mode in low-pressure glow discharges, and corresponds to the operation regime of most reported RF APGD experiments [1]- [7], [9], [16]. When the current density increases to a critical threshold, the discharge plasma evolves into a different operation regime in which the discharge current increases with decreasing gap voltage and the differential conductivity becomes negative [8].…”
Section: Current-voltage Characteristicsmentioning
confidence: 83%
“…Their operation is also very versatile, helped partly by their low-breakdown voltage. Through largely an engineering development, their application range and capability have been expanded considerably [1], [6], [9]. Yet there is a fundamental need for substantially advancing their basic understanding in order to aid not only the interpretation of complex experimental observations but also the development of their diagnostics methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently developed plasma arrays [22,[319][320][321][322][323][324] might be a good choice since the plasma area is much increased by integrating many microplasmas into one array. We can also use other large-area atmospheric-pressure plasmas [325][326][327][328][329][330][331][332][333] which are based on different designs.…”
Section: Removal Of Impurities and Large-scale Productionmentioning
confidence: 99%
“…Often this is realized in a jetlike configuration. [2][3][4][5][6][7][8][9][10][11] The vast majority of APGD jets reported so far employ sinusoidal excitation, although it has been known that nonsinusoidal excitation, through voltage pulsing, for example, offers a useful freedom to further improve APGD performance. 12 Initial results from few reported studies of pulsed APGD jets 4,10,13 have shown their general similarity to and contrast with sinusoidal APGD jets.…”
mentioning
confidence: 99%